The Safe and Effective Use of Shared Data Underpinned by Stakeholder Engagement and Evaluation Practice - Georgiou, Andrew; Magrabi, Farah; Hyppönen, Hannele; Wong, Zoie Shui-Yee; Nykänen, Pirkko; Scott, Philip J.; Ammenwerth, Elske; Rigby, Michael (Yearbook of Medical Informatics, 2018)
Objectives: The paper draws attention to: i) key considerations involving the confidentiality, privacy, and security of shared data; and ii) the requirements needed to build collaborative arrangements encompassing all stakeholders with the goal of ensuring safe, secure, and quality use of shared data.Method: A narrative review of existing research and policy approaches along with expert perspectives drawn from the International Medical Informatics Association (IMIA) Working Group on Technology Assessment and Quality Development in Health Care and the European Federation for Medical Informatics (EFMI) Working Group for Assessment of Health Information Systems.Results: The technological ability to merge, link, re-use, and exchange data has outpaced the establishment of policies, procedures, and processes to monitor the ethics and legality of shared use of data. Questions remain about how to guarantee the security of shared data, and how to establish and maintain public trust across large-scale shared data enterprises. This paper identifies the importance of data governance frameworks (incorporating engagement with all stakeholders) to underpin the management of the ethics and legality of shared data use. The paper also provides some key considerations for the establishment of national approaches and measures to monitor compliance with best practice.Conclusion: Data sharing endeavours can help to underpin new collaborative models of health care which provide shared information, engagement, and accountability amongst all stakeholders. We believe that commitment to rigorous evaluation and stakeholder engagement will be critical to delivering health data benefits and the establishment of collaborative models of health care into the future.
Keywords: Confidentiality; computer security; informed consent; evidence-based practice; program evaluation